EFFECTS OF FLOCK SIZE IN BROILERS REARED IN A FLOOR SYSTEM ON PERFORMANCE, SOME BLOOD PARAMETERS, BONE QUALITY AND MUSCULUS PECTORALIS PH LEVEL - Simsek, Ulku Gulcihan; Ozhan, Nejla (Walter de Gruyter Gmbh, 2015)
This research was conducted to compare performance, some blood parameters, bone quality and musculus pectoralis pH level in broiler flocks containing 15,000 (I), 25,000 (II) and 35,000 (III) birds. For this purpose, two different flocks from each capacity were simultaneously observed throughout two growth periods in summer and autumn seasons. A total of 20 broilers (10 males and 10 females) per different flock capacity, having stable live weight were selected on 32nd day of growing period. Broiler chickens were slaughtered by decapitation and their blood samples were drained into special tubes. Musculus pectoralis pH measurement was performed ten minutes after slaughter. Bones were extracted from meat and analyzed. Live weights of groups on days 1, 7, 14, 21, 28 and on the day of slaughter were similar to each other (P>0.05). The mortality rate was lower in group I (P <= 0.01). Feed efficiency deteriorated negligibly in group III (P=0.078). Serum glucose and uric acid levels were high in group III (P <= 0.01). Intergroup differences in serum total cholesterol, very-low-density lipoprotein cholesterol (VLDL), triglycerides, protein levels and enzyme activities of alkaline phosphatase and creatine kinase were statistically insignificant (P>0.05). Dimensions, weights and ash level of tibia and femur, bone mineral density (BMD) and bone mineral content (BMC) of tibia were observed to have similar values among the groups (P>0.05). Musculus pectoralis pH level in groups I, II and III was determined as 5.93, 5.94 and 6.13, respectively (P <= 0.05).
Keywords: broiler; flock size; performance; bone quality; welfare